The Physicochemical Quality of Traditional Burduf Cheese - Carmen Pop; Cristina Anamaria Semeniuc; Sorin Apostu; Ancuţa Mihaela Rotar (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology, 2013)
The aim of this study is the assessmentof the quality control of raw milk and traditional burduf cheese obtained fromcow milk mixed with 10% sheep milk. Appreciation of the integrity and freshness assessmentof milk (cow and sheep) was tested by physico-chemical analysis.On theshelf-live were determined the physico-chemical parameters in cheese samples. Theantibiotics residues were tested of the milk samples with portable analyser,model Rosa Charm Reader. Theresults of physico-chemical determinations for the milk and cheese samples werewithin the maximum permissible by data legislation. Regardingthe content of antibiotics, the results were negative both for cow milk and forsheep milk. The sensorycharacteristics of burduf cheese are influenced by the different types of milk.